Gamification in Teaching Entrepreneurship: The Role of Educational Technology - Mehdi Abbas; Syed Rizwan Ali; Dr. Ezanee Bin Mohamed Elias; Dr. Faisal Bin Zulhumadi (Al-Qanṭara, 2025)
This study dives into how the complicated business of learning to be entrepreneurs can be made more effective by adding some fun elements and digital tools. Taking the heart of this study are students’ motivation to engage with this new way of learning. Technology gets special treatment too because it seems to make all the difference. Using a quantitative approach with Structural Equation Modeling (SEM), data from 210 entrepreneurship students were analyzed to evaluate these relationships. Contrary to existing literature, the findings indicate that gamification did not significantly enhance student motivation, engagement, or overall teaching effectiveness in this specific context. Additionally, neither the expected mediation role of motivation nor the moderating influence of educational technology was observed. These unexpected results suggest that the effectiveness of gamification heavily depends on implementation quality, pedagogical alignment, and contextual factors rather than merely integrating game-like elements or technological tools. Recommendations are about paying attention to the careful design and merging integration of game thinking very carefully. Moving forward, researchers should cast a wider net with samples and take a multilevel look at longitudinal studies as well. They should also dig deep into specific strategies for gamification and explore the education techy side of things in an even more detailed way too.